Cinemasaurus : Russian film in contemporary context - Condee, Nancy; Prokhorov, Alexander, 1965-; Prokhorova, Elena (Film and media studies (Boston, Mass.), 2020)
"Cinemasaurus examines contemporary Russian cinema as a new visual economy, emerging over three decades after the Soviet collapse. Focusing on debates and films exhibited at Russian and US public festivals where the films have premiered, the volume's contributors-the new generation of US scholars studying Russian cinema-examine four issues of Russia's transition: (1) its imperial legacy, (2) the emergence of a film market and its new genres, (3) Russia's uneven integration into European values and hierarchies, (4) the renegotiation of state power vis-à-vis arthouse and independent cinemas. An introductory essay frames each of the four sections, with 90 films total under discussion, concluding with a historical timeline and five interviews of key film-industry figures formative of the historical context"--